Komunikasi dan Media Sosial (Communications and Social Media) - Watie, Errika Dwi Setya (Universitas Semarang, 2011)
Media presents to be a part of human life. The presence and the development of internet bring a new way of how to communite in social life. Social media presents and changes the communication paradigm in today's society. Communication in social media is not limited by distance, time, and space. It could happen anywhere, anytime, without having a face to face talking. Even social media can negate social status that is often as a barrier in communication.Social media has changed the world. Levels of communication merged into one container called a social media. The rise of many consequences must also be wary of, in the sense of social media opens up the opportunity of each individual involved in it to issue his opinion freely. However, self-control should be shared, in order to have freedom of communication which does not violate ethical boundaries and does not offend others.